Financial Reforms and Financial Development in Nepal: A Review - Pandey, Abhishek; Adhikari, Padma Kumar; Shrestha, Zenisha (Economic Review of Nepal, 2022)
Effective financial systems and institutions are foundational to the economic development of any country. Recognizing this, the Government of Nepal and the Nepal Rastra Bank (NRB) have embarked on numerous reforms aimed at bolstering the banking and financial sectors. These efforts are crucial for enhancing the efficiency, accessibility, and stability of financial services, which, in turn, spur economic growth. This study conducts a thorough review of the financial sector reforms initiated primarily by the NRB, detailing their scope and impact. It explores how these reforms have shaped the financial landscape of Nepal, aiming to create a more inclusive and competitive financial environment. Additionally, the research examines the current state of financial development across Nepal's provinces, identifying disparities in financial access and efficiency. This provincial analysis is vital for understanding the uneven distribution of financial services and its implications for regional economic growth. By evaluating the effectiveness of these reforms and the status of financial development, the study provides insights into the challenges and opportunities within Nepal's financial sector. It underscores the importance of continuous reforms, regulatory enhancements, and the promotion of financial literacy to achieve comprehensive financial development. The findings highlight the progress made thus far and the ongoing need for strategic policy interventions to ensure equitable economic development across all regions of Nepal, setting a pathway for future reforms.